2007
DOI: 10.1016/j.limno.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diatom, pollen, and chironomid assemblages in response to a recent volcanic event in Lake Galletué (Chilean Andes)

Abstract: Several lakes in Chile are near important volcanic areas where eruption impacts can limit the quality of lacustrine sediments for reconstructing past environmental changes. In this study, we report changes in diatoms, pollen, and chironomids assemblages after a tephra deposition in Lake Galletue´(Chilean Andes). A sediment core obtained from Lake Galletue´(40 m water depth) was sliced in 1 cm intervals and subsamples were taken to analyze each proxy. 210 Pb and 137 Cs activities were measured to obtain the geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Changes to the diversity and abundance of diatom and chironomid assemblages following tephra deposits have been recorded elsewhere in the Andes (Urrutia et al, 2007;Massaferro and Corley 1998). In Laguna Baños, Cocconeis placentula records the single largest change in species relative abundance (>20%) between adjacent intervals (Fig.…”
Section: Response To Volcanismmentioning
confidence: 86%
See 2 more Smart Citations
“…Changes to the diversity and abundance of diatom and chironomid assemblages following tephra deposits have been recorded elsewhere in the Andes (Urrutia et al, 2007;Massaferro and Corley 1998). In Laguna Baños, Cocconeis placentula records the single largest change in species relative abundance (>20%) between adjacent intervals (Fig.…”
Section: Response To Volcanismmentioning
confidence: 86%
“…Rather, immediately above the tephra layer, chironomid head capsules were absent and abundances remained low until 20-cm depth. A decrease in the concentration of head capsules following a tephra deposit was recorded in Andean lakes from Chile and Argentina (Urrutia et al, 2007;Massaferro and Corley 1998). This drop in abundance in the sediments following the tephra may be due to disruptions to chironomid habitat and food supply.…”
Section: Response To Volcanismmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that the interaction of volcanic ash deposition with a receiving lake triggers perturbations, primarily through the effect of tephra weathering but also through changes in pH, mineral concentration, organic matter input, and short-term light deprivation (e.g., Harper et al, 1986;Barker et al, 2003;Telford et al, 2004;Cruces et al, 2006;Urrutia et al, 2007;D'Addabbo et al, 2015). Depending on the magnitude of the disturbance and the resilience of the respective ecosystem (i.e., the amount of disturbance an ecosystem can tolerate without changing its regime; Holling et al, 1973Holling et al, , 1986Scheffer and Carpenter, 2003;Baho et al, 2014), lake biota may react with extinction events and/or changes in community structures and functions.…”
mentioning
confidence: 99%
“…Confounding events of ecoclimatic diatom assemblages may be rare, but significantly large, volcanic tephra influx has affected diatom community relative abundance and composition in lakes elsewhere (BARKER et al, 2000, 2003, BARSDATE and DUGDALE, 1972, BERTRAND et al, 2005, BIRKS and LOTTER, 1994, CRUCES et al, 2006, KILIAN et al, 2006, LOTTER et al, 1995, TELFORD et al, 1999, 2004, URRUTIA et al, 2007, VOLLAND 2006, WISSMAR et. al., 1982.…”
Section: Introductionmentioning
confidence: 99%